Legitimacy and accountability of state systems: New challenges - Bhambhri, C.P. (1995)
"Following an examination - at conceptual level - of various factors presently eroding State's legitimacy, the author focuses on the scenario of the Indian State. He identifies and examines various significant factors, thrown up in various studies on the subject, that are causing serious turmoil. He then highlights the immediate need of extendingt due share of economic benefits to the deprived majority - who in his view have become democratically assertive - in the interest of restoring and strengthening credibility of the Indian State"
Keywords: Administrative responsibility - India; Public administration - India; Public administration